Characterization of Methicillin-Resistant Staphylococcus aureus Isolates from Patients with Persistent or Recurrent Bacteremia. Issue 2 (2014) - Wong, Henry; Watt, Christine; Elsayed, Sameer; John, Michael; Johnson, Glen; Katz, Kevin; Krajden, Sigmund; Lee, Christine; Mazzulli, Tony; Ostrowska, Krystyna; Richardson, David; Toye, Baldwin; et al.
Abstract : BACKGROUND: Methicillin-resistant Staphylococcus aureus (MRSA) bloodstream infections (BSI) are associated with considerable morbidity and mortality, especially with persistent (PB) or recurrent bacteremia (RB). OBJECTIVE: To determine the frequency of PB and RB in patients with MRSA BSI, and to characterize the isolates from these patients. METHODS: Surveillance for MRSA BSI was performed for one year in 13 Canadian hospitals. PB was defined as a positive blood culture that persisted for ≥7 days; RB was defined as the recurrence of a positive blood culture ≥14 days following a negative culture. Isolates were typed using pulsed-field gel electrophoresis (PFGE). Vancomycin susceptibility was determined using Etest. RESULTS: A total of 183 patients with MRSA BSI were identified; 14 (7.7%) had PB and five (2.7%) had RB. Ten (5.5%) patients were known to have infective endocarditis, and five of these patients had PB or RB. Initial and subsequent MRSA isolates from patients with PB and RB had the same PFGE type. There were no significant differences in the distribution of PFGE types in patients with PB or RB (37% CMRSA-2/USA100; 37% CMRSA-10/USA300) compared with that in other patients (56% CMRSA-2/USA100; 32% CMRSA-10/USA300). All isolates were susceptible to vancomycin, but patients with PB or RB were more likely to have initial isolates with vancomycin minimum inhibitory concentration = 2.0 μg/mL (26% versus 10%; P=0.06). CONCLUSIONS: Persistent or recurrent MRSA bacteremia occurred in 10.4% of patients with MRSA BSIs. Initial isolates from patients with persistent or recurrent MRSA BSIs were more likely to exhibit reduced susceptibility to vancomcyin, but were not associated with any genotype.